SWOT ANALYSIS OF THE SERVICE DEVELOPMENT STRATEGY FOR PUTRI HIJAU TYPE II HOSPITAL IN MEDAN - Priscilia Ade Syahna; Ermi Girsang; Sri Lestari Ramadhani Nasution (Journal of Gender and Social Inclusion in Muslim Societies, 2026)
The hospital industry faces intense competition and rapid technological changes. Military-affiliated hospitals, such as Putri Hijau Type II Hospital in Medan, must balance their dual role of serving both military personnel and the general public under the national health insurance scheme while maintaining a competitive edge. This study aims to analyse the strategic position of Putri Hijau Type II Hospital and formulate service development strategies using a SWOT-based analytical approach. A mixed-methods case study design was employed. Data were collected through interviews with management, field observations, and structured questionnaires. Analysis was conducted using Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and the Internal-External (IE) Matrix. The research findings indicate that the hospital holds a strong internal position (IFE score: 2.86) and adequate external responsiveness (EFE score: 2.51). Positioned in Quadrant I (Grow and Build), the institution is recommended to pursue an aggressive strategy. Key strengths include clinical professionalism and military discipline, while primary weaknesses involve infrastructure constraints and service wait times. To maintain market dominance, the hospital must prioritise digital transformation and infrastructure modernisation to synergise its humanistic care with operational efficiency.